2021
DOI: 10.1155/2021/4133892
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Audience Evaluation and Analysis of Symphony Performance Effects Based on the Genetic Neural Network Algorithm for the Multilayer Perceptron (GA‐MLP‐NN)

Abstract: Traditional symphony performances need to obtain a large amount of data in terms of effect evaluation to ensure the authenticity and stability of the data. In the process of processing the audience evaluation data, there are problems such as large calculation dimensions and low data relevance. Based on this, this article studies the audience evaluation model of teaching quality based on the multilayer perceptron genetic neural network algorithm for the data processing link in the evaluation of the symphony per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The MLP-NN concepts are used even for different areas of interest. An audience evaluation system was introduced in [ 12 ]. It studies a model for the teaching audience evaluation system based on the multilayer perceptron.…”
Section: Related Workmentioning
confidence: 99%
“…The MLP-NN concepts are used even for different areas of interest. An audience evaluation system was introduced in [ 12 ]. It studies a model for the teaching audience evaluation system based on the multilayer perceptron.…”
Section: Related Workmentioning
confidence: 99%
“…They have characteristics of organization, adaptive, and learning, which can be applied to solve complex problems effectively, which is difficult to be solved by traditional optimization algorithms. Some of the renowned algorithms are genetic algorithm (GA) [ 3 ], differential evolution (DE) [ 4 ], estimation of distribution algorithms (EDA) [ 5 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%